PENGARUH NUMBERED HEAD TOGETHER (NHT) DENGAN METODE DEMONSTRASI DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA PADA MATERI BANGUN DATAR KELAS VIII DI SMP SWASTA FREE METHODIST 1 MEDAN T.A 2023/2024 - Pasaribu, Jonson Jusufri; Simanjuntak, Ruth Mayassari; Simbolon, Lolyta Damora (Universitas Quality, 2024)
This study aims to determine whether there is an effect of the Numbered Head Together (NHT) model with the Demonstration Method in improving students' mathematical concept understanding ability in class VII of SMP Swasta Methodist Merdeka 1 Medan. The type of research used in this research is Quasi experiment with test instruments. The population in this study were all VII grade students of SMP Swasta Methodist Merdeka 1 Medan consisting of 4 classes. By using cluster random sampling technique, the samples in this study were class VII-2 as the experimental class and class VII-3 as the control class. Based on calculations in the experimental class, the ability to understand mathematical concepts has an average value of = 76.03. In the control class, the ability to understand mathematical concepts of students has an average value of = 58.63. By looking at the average results of the abilities obtained between the two classes, it can be concluded that the Numbered Head Together (NHT) model with the Demonstration method has a higher effect than the conventional learning model on the ability to understand students' mathematical concepts on the material of Square Flat Buildings in class VII SMP Swasta Methodist 1 Medan.